O retrato feminino na escultura portuguesa dos séculos XIX e XX : um percurso escultórico - Ribeiro, Ana, 1994- (2018)
In this Master’s dissertation we will approach the sculptural tipology of the female portrait in the portuguese sculpture of the end of the 19th century and on of 20th century. In order to understand the different views over this subject, we will give an international context to the subject, beginning with the classical Antiquity utill the 20th century. There will be, a more detailed analysis concerning the roman portrait, not only because of its large diffusion but also for its legacy, like no other period in history of sculpture the portrait was so important. In another moment, the focus will be on the portrait in Portugal, emphasizing the refered periods. The second part is composed by a sculptoric set of 25 portraits belonging to 16 different sculptors. The choice was based on a personal selection having in count an inventory of about 251 female portraits. Each portrait will be analyse and also a short biography of the sculptors will be present. We will start at the year of 1881 with Flor Agreste, from Soares dos Reis and finish in 1999 with the bust of Natália Correia, from João Cutileiro. This set englobes different age ranges, corresponding to anonymous people, detached people from the national scene, as well as artists’ relatives and friends. With all this diversity, it is possible to understand the artistic qualities but also the formal changes present in portraits, accorrdingly to the time they were executed. The main goal of this Master dissertation is to understand the act of portray and how it can changes depending on time and sculptor